Simulation of a muographic analysis of a volcanic dome in Geant4 - Athanassas, Constantin D.; Kitsaki, C.; Alexopoulos, T.; Gika, V.; Maltezos, S. (HNPS Advances in Nuclear Physics, 2020)
Here we present a Monte Carlo simulation of a muographic campaign on Methana volcano, Greece. In order to estimate the absorption parameters and the pattern of muon scattering at various incident energies (GeV to TeV), a radar-derived digital terrain model (DTM) was submitted to irradiation by horizontal muons in Geant4 and the penetrating muons were collected by a hypothetical MicroMegas particle detector on the other side of the DTM. Monte Carlo simulation demonstrated that muon energies at least as high as 10 TeV are required for whole-scale radiography of Methana and one has to reduce the scale of study to smaller structures (e.g. ~ 600 m - wide volcanic domes) in order to exploit the more affluent lower energy muons (~ 600 GeV).  Coulomb scattering, on the other hand, brings about deflection of muon trajectories away from the detector, resulting in loss of information. Additionally, scattering adds Gaussian blurring to the scanned objects. With the intention of improving contrast and extract objects in muographic image we recommend the use of spatial operators (filters) employed in image analysis.